PENGARUH KOMITMEN AFEKTIF, KOMITMEN BERKELANJUTAN, KOMITMEN NORMATIF TERHADAP KINERJA KARYAWAN MELALUI VARIABEL ORGANIZATION CITIZENSHIP BEHAVIOR (OCB) SEBAGAI VARIABEL INTERVENING PADA PT. TEMPRINA MEDIA GRAFIKA SEMARANG - Evan Tree; Sri Suryoko (Jurnal Ilmu Administrasi Bisnis, 2016)
ABSTRACT            The economic activities that really dynamic make company must active to change and create new strategy to make company sustain, human resource have dominant role in company activities, PT. Temprina Media isone of printing company in Semarang, based on observation performance each of employee really fluctuating and company often change the regulation and procedure that affect to the employee and fact. point of success of company depends on talent performance which determines the achievement of organization goals. Talent not only have good competence but behaviors that show high contribution and Organization Citizenship Behavior (OCB). Organization Citizenship Behavior (OCB) is a behavior that appear because of high commitment. Therefore to increase organization commitment will influence OCB in employee’s. This research aims to analyze the influence of affective commitment, continuous commitment, and normative commitment on employee’s performance through OCB as an intervening variable. This study used multiple linear regression analysis using SPSS. The population used is a Employee’s of PT. Temprina Grafika Media Semarang with the number 44. The amount of sample used as many as 44 people, it is called a census study. The results showed that there is positive and significant correlation between each organization commitment variable (affective, continuous, normative) on OCB and Employee’s performance, there is positive and significant correlation between OCB on Employee’s Performance, and there is positive and significant correlation between Continuous Commitment and Affective Commitment on Employee’s Performance through OCB.. Advice for this research is company must maintain employee’s commitment and OCB by make strategic through shaping culture, make unique engagement and management of employee also make improvement term of data management to ensure their performance and experience.